Screening of factors affecting biohydrogen production from sago wastewater - Mohamad Puad, Noor Illi; Ulhiz, Tami Astie; Azmi, Azlin Suhaida (2017)
Introduction: Untreated sago waste water (SWW) contains high organic content which can cause severe environmental pollution. SWW that has not fully utilized is a potential susbstrate for biohydrogen production due to its starch content. We took SWW from Batu Pahat, Johor which contains COD and glucose. After acid pretreatment process the glucose was further increased significantly. pH, temperature, inoculum size, malt extract, yeast extract, metals concentration, and nitrogen sparge were factors investigated in this experiment. This study aims to select 3 most significant factors that affect biohydrogen production Methodology: Enterobacter aerogenes (E. aerogenes) was used in this experiment as a hydrogen producing bacterium. Initially, the bacteria were cultured in 100 ml LB medium in the flask. The flask then was placed in an incubator shaker at 150 rpm with the temperature of 35oC for 18 hours. Acid pre-treatment of SWW was carried out using 1.5% v/v H2SO4 at 121oC for 60 in an autoclave The acidic SWW was then neutralized to pH designed for this experiment. The experiments were conducted in 125 ml serum bottles with a 80 ml working volume. Before fermentation was carried out, the prepared SWW was supplemented by modified endonutrient. After it was ready, inoculum, malt extract, yeast extract, FeSO4.7H2O, MgSO4.7H2O, and CuCl2.2H2O were added under sterile condition. The bottle was then purged by nitrogen gas and sealed with silicone stopper and alumunium cap. Fermentation was carried out using parameters according to Plackett Burman design. All experiments were conducted in incubator shaker at 48 hours with the agitation speed of 125 rpm. The bacterial growth was determined using colony cell counting. The gas was collected using 50 ml gas tight syringe. Hydrogen concentration was measured using hydrogen analyzer. Initial and final glucose concentration was recorded using HPLC Findings: SWW contains 460 mg/L COD and 0.084 g/l glucose . After acid pretreatment the glucose content was 40.88 g/l. The inoculum stock contains bacteria with OD600 of 4.5. It was found that from 10 phsyco-chemical factors, yeast extract concentration, fermentation temperature, and inoculum size were ranked as the most significant factor. Positive effect of yeast extract indicated that the more yeast extract added to the media, the higher the concentration of hydrogen produced. While the effect of inoculum and temperature was negative, indicating that less inoculum size and temperature was more preferable to achieve high hydrogen concentration. The model suggested that 36.76 µmol hydrogen can be produced by using these parameters; pH 7.25, temperature 35oC, inoculum size 5.19%, malt extract 1.97 g/l, yeast extract 2.00 g/l, iron 200 mg/l, magnesium 288.36 mg/l, cuprum 6 mg/l, without sparging of nitrogen. The maximum hydrogen concentration, volume production, and hydrogen yield were 36.34 µmol, 88 ml, and 2.41 mmol H2/mol glucose respectively, obtained from run no 10. Contribution: Bacteria prefer glucose for hydrogen generation. However, the use of glucose from biomass feedstock is more preferred for bioethanol production, which gives higher yield and conversion rate than biohydrogen. In recent years, there has been an increasing interest in waste due to the cost effectiveness and renewability. Sago waste is one of the potential candidate that is available abundantly in Malaysia. However, the researches of biohydrogen production from sago waste are still limited, especially using single culture of E. aerogenes. Therefore, this paper is trying to fill the gap by investigating which factors are mostly significant to optimize hydrogen production from sago waste